(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
In the scientific article, the effect of covering the seeds of local cotton varieties Gossipium barbadense with bentonite slurry on the seed germination was studied in the growing barren soils of the Surkhandarya region of the Republic of Uzbekistan. When coating cotton seeds with bentonite clay solution, when 50 kg of seeds are coated with 15 kg of melted bentonite mud, the dynamics of seed germination and the effect on cotton growth and yield are described. Differences in growth and development of treated seeds of domestic and imported thin-fiber cotton varieties compared to untreated variants were determined during the season. Also, the effects of planted cotton varieties on the yield and quality of the crop were determined, and the differences between the control and the varieties were studied. It has been studied that bentonite clay is an agro-ore rich in natural micronutrients, and due to its good adsorbent properties, it can increase the tolerance of seeds to various stress and extreme conditions encountered in the soil during the germination period, and also increase the resistance to the negative effects of diseases and pests. In the scientific article, information on the new, cheap and effective technology of planting seeds with a bentonite clay solution of natural non-traditional agro-ore is presented based on research.